The Diversion of Human Energy: How Work Has Become a Commodity in Modern Societies - João Carlos Orquiza (Current Progress in Arts and Social Studies Research Vol. 2, 2024)
This essay explores the transformation of human energy from a resource for subsistence and social cohesion into a tradable commodity in modern societies. In a universe dominated by the second law of thermodynamics, where entropy is an inescapable constant, life fundamentally challenges this tendency by maintaining order and complexity through free energy. Human energy, generated incessantly and autonomously by the cells of the human body, is not only the vital force sustaining biological processes but also the primary source of energy fueling the complex structures and operations of contemporary societies. This essay proposes an innovative hypothesis and, in theoretical and conceptual terms, proves that the true commodity in modern societies is human energy, not merely human labour. The comparison between human energy and oil as essential commodities offers a new perspective on the centrality of human energy in the global economy. Additionally, the econometric model presented quantifies the contribution of human energy to economic production, highlighting its irreplaceable importance.